Revealing structural modifications in thermomechanical reshaping of collagenous tissues using optical coherence elastography. Issue 3 (9th December 2018) - Zaitsev, Vladimir Y.; Matveyev, Alexander L.; Matveev, Lev A.; Gelikonov, Grigory V.; Baum, Olga I.; Omelchenko, Alexander I.; Shabanov, Dmitry V.; Sovetsky, Alexander A.; Yuzhakov, Alexey V.; Fedorov, Anatoly A.; Siplivy, Vladimir I.; Bolshunov, Andrey V.; et al.
Abstract : Moderate heating of such collagenous tissues as cornea and cartilages by infra‐red laser (IR laser) irradiation is an emerging technology for nondestructive modification of the tissue shape and microstructure for a variety of applications in ophthalmology, otolaryngology and so on. Postirradiation high‐resolution microscopic examination indicates the appearance of microscopic either spheroidal or crack‐like narrow pores depending on the tissue type and irradiation regime. Such examinations usually require special tissue preparation (eg, staining, drying that affect microstructure themselves) and are mostly suitable for studying individual pores, whereas evaluation of their averaged parameters, especially in situ, is challenging. Here, we demonstrate the ability of optical coherence tomography (OCT) to visualize areas of pore initiation and evaluate their averaged properties by combining visualization of residual irradiation‐induced tissue dilatation and evaluation of the accompanying Young‐modulus reduction by OCT‐based compressional elastography. We show that the averaged OCT‐based data obtained in situ fairly well agree with the microscopic examination results. The results obtained develop the basis for effective and safe applications of novel nondestructive laser technologies of tissue modification in clinical practice. PICTURE: Elastographic OCT‐based images of an excised rabbit eye cornea subjected to thermomechanical laser‐assisted reshaping. Central panel shows resultant cumulative dilatation in cornea after moderate ( 45‐50°C) pulse‐periodic heating by an IR laser together with distribution of the inverse Young modulus 1/ E before (left) and after (right) IR irradiation. Significant modulus decrease in the center of irradiated region is caused by initiated micropores. Their parameters can be extracted by analyzing the elastographic images. Abstract : Elastographic OCT‐based images of an excised rabbit eye cornea subjected to thermomechanical laser‐assisted reshaping. Central panel shows resultant cumulative dilatation in cornea after moderate ( 45‐50C) pulse‐periodic heating by an IR laser together with distribution of the inverse Young modulus 1/E before (left) and after (right) IR irradiation. Significant modulus decrease in the center of irradiated region is caused by initiated micropores. Their parameters can be extracted by analyzing the elastographic images.